FENOMENA IKLAN TERHADAP KAUM MUDA Sebuah Tinjauan Pastoral menurut Dokumen Christus Vivit Art. 79 - Eric Yohanis Tatap (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2022)
Young people are currently experiencing a crisis where advertisements are scattered here and there. Advertisements streak human life and people know everything just by looking at advertisements. However, advertising also has a dark side: it provides false information. Therefore, this article aims to explore the phenomenon of advertising that is rife in human life and especially affects young people. His finding was to design a strong pastoral structure to help the young people of the Church live out their faith in the person of Jesus Christ the True Advertiser. The method used in this paper is to use qualitative methods by means of literature study with the aim of helping to decipher the problems that are happing